CAGED WOMAN IN THE MILITAR TIME: WOMAN REPRESENTATION AS MARGINALIZED PERSON IN O PARDAL E UM PASSARO AZUL, BY HELONEIDA STUDART - Mello, Evelyn Caroline de [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2018)
This article intends to show the process of construction about the females characters in the novel O pardal e um passaro azul de Heloneida Studart, wrote and published in the Militar time (1964 - 1985) in Brazil. For that, this work is based on the feminist theory, because the protest against the Dictatorship and the contestation against the female oppression are present at the same time in the novel, especially in the character characterization and in the narrative focus.
Keywords: Feminism; female characters; Heloneida Studart